Using Math Journals in a Grade 3/4 Classroom - Karen Scales (Networks: An Online Journal for Teacher Research, 2000)
The purpose of this study was to examine how the use of math journals could facilitate modifications in instructional practice. The specific research questions were: Are math journals an effective diagnostic tool? Do they provide information not already provided through traditional assignments? How can they be used in assessment?